The Association of Central corneal thickness with Intra- ocular Pressure of human being in AL Sadder Medical city - Abdulmohsin Ali Almashref, Sabah; Hussein Ali Al-Maleki, Qusay; Abd Abd Ali Alshamkie, Kassim (International Journal of Psychosocial Rehabilitation, 2022)
Between intraocular pressure and central corneal thickness of 200 eye of 100 subjects consisting of males (n=53) (53%), and females (n=47) (47%) within ( 18-75) years with, mean age of (47.6±12.961) years. For all the subjects, mean corrected IOP (18.44±6.4575) mmHg. Mean CCT (524.775±41.796) μm. Mean corrected IOP for males (18.3113±6.48503) mmHg, and for females mean corrected IOP (18.5851±6.47123) mmHg. The CCT for males (525.5283±45.39594) μm and for females (523.92536±37.56521) μm. The study was shown that there is no liner relationship between IOP and CCT and the relation is inverse and not significant. It was also shown that neither CCT nor IOP was influenced by gender. And there was no difference between right and left eye. There was strong positive correlation between RT.CCT and LT.CCT. The slight association between CCT and age indicated a reduction of CCT with increasing age.